(An)other space is possible : an exploration of the conflicts and contestations in the realisation of a “democratising” Public Space in the City of Tshwane - Landman, Karina (University of Pretoria, 2022)
Thesis (PhD (Town and Regional Planning))--University of Pretoria, 2021.